1999
DOI: 10.1002/(sici)1097-4636(1999)48:5<621::aid-jbm5>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a collagen matrix containing basic fibroblast growth factor on wound contraction

Abstract: We evaluated the effectiveness of basic fibroblast growth factor (bFGF) in inhibiting wound contraction, both alone and in combination with collagen matrix, using a simulated in vivo delayed healing type model. We also studied the mechanisms involved in this inhibition in in vitro experiments using fibroblast populated collagen gels. As a result, we were able to demonstrate that both collagen matrix and bFGF significantly inhibited wound contraction; especially, bFGF acted in a dose-dependent fashion. Interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 33 publications
3
61
0
Order By: Relevance
“…There are numerous studies that report inhibition of wound contraction after implanting a collagenous ECM into full-thickness wounds. 6,[77][78][79][80][81] This effect is used, and indeed desired, in human wound treatment, where contraction is usually unwanted. In veterinary applications, however, contraction is often a welcome and important attribute of open wound management, unless the wounds are over flexor and extensor aspects of joints, and adjacent to orifices.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous studies that report inhibition of wound contraction after implanting a collagenous ECM into full-thickness wounds. 6,[77][78][79][80][81] This effect is used, and indeed desired, in human wound treatment, where contraction is usually unwanted. In veterinary applications, however, contraction is often a welcome and important attribute of open wound management, unless the wounds are over flexor and extensor aspects of joints, and adjacent to orifices.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, one of the approaches to minimize scarring is to increase the tensile strength via wound dressing materials. 3D collagen sponges have been used alone 145,146 or in conjunction with basic fibroblast growth factor, 147 fibronectin or hyaluronic acid. 148 Exogenous collagen increased wound tensile strength and increased degree of reepithelialization i.e., early dermal and epidermal wound healing.…”
Section: Cellular Interactionmentioning
confidence: 99%
“…18,19 In addition, application of bFGFcontaining collagen sponges in full-thickness wounds reduced aSMA expression and wound contraction in a rat model. 29,30 In agreement, we showed that treatment of HFCs with bFGF decreased aSMA fibers significantly and diminished the ability of these cells to contract fibrin. Interestingly, the effect of bFGF on P-aSMA was less dramatic.…”
mentioning
confidence: 99%